2009
DOI: 10.1136/ip.2008.019851
|View full text |Cite
|
Sign up to set email alerts
|

Safety behaviours among Alaskan Native and American Indian people living in Alaska

Abstract: Recommendations for future injury prevention efforts in this population are to increase use of personal flotation devices while boating and address the underuse of helmets with off-road vehicles. Limited prevention resources should be used to target those who engage in risky behaviours to maximise programme impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Other studies were less consistent, showing an increase in lifejacket use by age among Alaskan and American indigenous adults [ 27 ]. Quistberg et al [ 29 ] found differences in lifejacket use by age with those aged 30 to 59 years more likely to wear lifejacket than their younger and older counterparts; these differences were not statistically significant.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies were less consistent, showing an increase in lifejacket use by age among Alaskan and American indigenous adults [ 27 ]. Quistberg et al [ 29 ] found differences in lifejacket use by age with those aged 30 to 59 years more likely to wear lifejacket than their younger and older counterparts; these differences were not statistically significant.…”
Section: Resultsmentioning
confidence: 99%
“…Rates of helmet nonuse and of related injury appear to vary across population subgroups. For example, children living in rural areas, including young people in northern, remote, and agricultural settings where ATV and snowmobile use are common, experience significantly higher risks for off‐road vehicular‐related injury 25–29 . Young males are more likely to ride, and to be injured, than are females 30 .…”
mentioning
confidence: 99%
“…For example, children living in rural areas, including young people in northern, remote, and agricultural settings where ATV and snowmobile use are common, experience significantly higher risks for offroad vehicular-related injury. [25][26][27][28][29] Young males are more likely to ride, and to be injured, than are females. 30 In order to examine these differences further and possibly shed some light on the mechanisms underlying them, we designed this national study to examine off-road vehicle and related helmet use, not only in an aggregate sense, but disaggregated by 5 sociodemographic characteristics known to be associated with the identification of vulnerable groups: age, gender, socioeconomic status, urbanrural status, and how long the young people have lived in Canada.…”
mentioning
confidence: 99%
“…The terms cultural competency, cultural appropriateness, and cultural sensitivity are often deployed in articles that discuss the importance of culture in injury prevention efforts. Cultural sensitivity and appropriateness in particular are often used interchangeably, or jointly, and authors typically make no reference to an exact definition of either term(cf, Irie, Pollard, & Bellamy, ; Redwood et al., ). Existing literature, nevertheless, does provide clear examples of culturally competent, appropriate, and sensitive programs that illustrate the practical application of these concepts to injury prevention, an area in which public health nurses wield large influence.…”
mentioning
confidence: 99%